Modeling employees' skills for sustainable banking services - Azizzadeh, Fariba; Islam, Mohammad Shahidul; Naushin, Najeebah; Zupok, Sebastian; Soboń, Dariusz; Soboń, Janusz; Selezneva, Ruslana; Jadah, Hamid Mohsin (Frontiers in Sociology, 2022)
Data to contribute to sustainable banking services are still ambiguous in Bangladesh. Therefore, the qualitative exploration of bank employees' skills to advance contemporary banking careers and services has been rational. Besides, limited knowledge of suggesting a sustainable banking career and service urges this study to adapt to New Normal Post-Covid-19. Fifteen experienced employees from the banking industry participated in the interview to accomplish the research. The results from content data analysis show that technical skills may vary from department to department based on job responsibilities. However, the employee skills are more or less the same for different banks. The results further show that the banking people put significant weight on the honesty of banks' employees as the banks maintain a large amount of cash and other types of assets in their vaults. Additionally, the research participants expressed their sentiments about other skills such as patience, smartness, and technological expertise. These skills are needed to carry out the day-to-day operations and earn a high level of customer satisfaction. The study, therefore, suggests banks focus on creating an employee base having the skills found from the investigation to develop banking services.